Polymorphisms in the advanced glycosylation end product-specific receptor gene and risk of incident myocardial infarction or ischemic stroke - Zee, Robert Y L; Romero, Jose R; Gould, Jessica L; Ricupero, Dennis A; Ridker, Paul M (Stroke (1970), 2006)
Recent findings of an association between polymorphisms of advanced glycosylation end product-specific receptor (AGER) and risk of diabetic vasculopathy have generated great interest. However, to date, no genetic-epidemiological data are available on risk of atherothrombotic events among nondiabetic populations. Using DNA samples collected at baseline in a prospective cohort of 14,916 initially healthy American men, we evaluated 3 AGER genetic variants: -429T>C, -374T>A, and Gly82Ser, among 600 white individuals who subsequently developed atherothrombotic event (incident myocardial infarction or ischemic stroke) and among 600 age- and smoking-matched white individuals who remained free of reported vascular disease during follow-up (controls). Genotype distributions for the polymorphisms tested were in Hardy-Weinberg equilibrium. Haplotype-based conditional logistic regression, adjusting for other potential confounders, showed that haplotype C-T-Gly (myocardial infarction: odds ratio [OR], 0.60; 95% CI, 0.41 to 0.90; P=0.01) and haplotype T-A-Gly (ischemic stroke: OR, 0.63; 95% CI, 0.40 to 0.99; P=0.05), compared with the reference haplotype T-T-Gly, were associated with reduced risk of atherothrombosis. Prespecified analysis limited to those without baseline history of diabetes showed similar significant findings. We found an association of specific AGER promoter gene haplotypes with reduced risk of incident myocardial infarction and ischemic stroke that was independent of the presence of diabetes.